Natural factors and their impact on human security - Ahmed, Salwa Hassan (Journal of natural sciences, life and applied sciences, 2023)
This study dealt with the natural factors which affect human life and safety, in order to find ways to meet the challenges of the environment towards human security. The main objective of the present study is to investigate the facts about the natural conditions which affect the security of peoples and which constitute natural disasters for humans’ survival on earth. To know them and their role in human security in the present and the future, this paper aimed to clarify these natural factors to draw the attention of the competent authorities to develop appropriate solutions to get out of the natural crises that affect human security and work to confront the impact of natural phenomena in order to preserve the security of peoples. The study followed the descriptive analytical approach to describe the natural phenomena, describing and analyzing their data to come up with clear findings and evidence to reveal aspects of its impact on the security of peoples. The study came out with several results, the most important of which is that the elements of the climate play a vital role in destabilizing the security of humans, such as the excessive decrease or increase of temperature, rainfall or winds or the emission of atmospheric energies, whether chemical or nuclear, and which are considered the most dangerous destructive energies for the lives of peoples, in the present and in the future, and the union of nitrogen with oxygen to form nitrogen oxide and its role in causing respiratory diseases, in addition to the effect of kinetic energy represented in floods and the movement of winds and their role in the transmission of epidemics and diseases, and the spread of effects of earthquakes, volcanoes, cracks and the role of gravity as a catalyst for these natural phenomena and what they play in the destruction of humans and their material and in-kind property. The study came out with several recommendations, including working to avoid the problems of increasing or decreasing climate elements and building windbreaks in arid and semi-arid regions to prevent the movement of winds that destroy the vital environment, in addition to their role in transmitting diseases that threaten the security of peoples and proper planning for human habitation away from places of mountains and rocky masses in anticipation of any landslides due to gravity and avoiding the establishment of experiments and industries that depend on nuclear and chemical energy near human residential places.
Keywords: human; environment; security; natural phenomena; environmental pollution